How publics in small-island states view climate change and international responses to it - Matto Mildenberger; Sara M. Constantino; Paasha Mahdavi; Parrish Bergquist; Gabriel De Roche; Emma Franzblau; Cesar Martinez-Alvarez; Ingmar Sturm (Proceedings of the National Academy of Sciences, 2025)
Climate change caused by carbon pollution from the world’s largest economies poses an existential threat to small-island states and territories this century. These places bear virtually no responsibility for climate change but will face sea-level rise, fresh water resource degradation, and intensified storms that will kill or dislocate exposed publics, and damage local economies. To alleviate this crisis, the global community has begun discussing who is responsible for climate mitigation and adaptation costs for those affected by climate change, in addition to continued debates around the distribution of responsibility for climate change. Missing from this analysis, however, are systematic efforts to elicit the preferences and perceptions of publics in these threatened small-island states and territories. Here, we report results from a large-sample (n = 14,710) cross-national survey of publics living in climate-vulnerable states and territories, conducted in June–July 2022. By quota sampling through Facebook’s ad platform, we generate survey samples at the national or territorial level for publics in 55 small-island states, territories, and subnational regions in the South Pacific, Indian Ocean, and Caribbean. We find widespread awareness and concern about the threat posed by climate change and sea-level rise, in contrast to what existing research finds in the Global North. We also find that climate-vulnerable publics believe their home governments, large polluters, and former colonial powers are all responsible for helping to manage the climate crisis, irrespective of these actors’ relative carbon emissions. These findings fill an important gap by depicting climate beliefs among the communities at the frontlines of climate change.